2017
DOI: 10.1002/cpt.620
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval Shortening With Isavuconazole: In Vitro and In Vivo Effects on Cardiac Repolarization

Abstract: The effects of isavuconazole (active moiety of isavuconazonium sulfate) on cardiac ion channels in vitro and cardiac repolarization clinically were assessed in a phase I, randomized, double‐blind study in healthy individuals who received isavuconazole (after 2‐day loading dose), at therapeutic or supratherapeutic doses daily for 11 days, moxifloxacin (400 mg q.d.), or placebo. A post‐hoc analysis of the phase III SECURE trial assessed effects on cardiac safety. L‐type Ca2+ channels were most sensitive to inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 25 publications
2
47
1
1
Order By: Relevance
“…Importantly, a number of clinical, pharmacokinetic, pharmacodynamic, safety and ease-of-use benefits have been documented with the use of isavuconazole, which fall outside of the scope of the model described here. For example, unlike voriconazole which may extend the QT interval, isavuconazole has a dose-related shortening effect, with no evidence of associated cardiac risk, thereby potentially reducing the cost of cardiac-associated AEs 67 . Additionally, isavuconazole has fixed dose administration via either oral capsules or an intravenous infusion 33 , whereas voriconazole must be administered twice daily, which will likely lead to increased costs associated with drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a number of clinical, pharmacokinetic, pharmacodynamic, safety and ease-of-use benefits have been documented with the use of isavuconazole, which fall outside of the scope of the model described here. For example, unlike voriconazole which may extend the QT interval, isavuconazole has a dose-related shortening effect, with no evidence of associated cardiac risk, thereby potentially reducing the cost of cardiac-associated AEs 67 . Additionally, isavuconazole has fixed dose administration via either oral capsules or an intravenous infusion 33 , whereas voriconazole must be administered twice daily, which will likely lead to increased costs associated with drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotoxicity: QT prolongation is a standard parameter to study cardiac abnormalities 103 . Further, prolongation of QT may be responsible for the sudden death and it is called Torsade de Pointes 104 .…”
Section: Trigger Of Torsade De Pointis Andmentioning
confidence: 99%
“…The drug has been approved by the US and the European regulatory agencies in 2016. While azoles as a class effect are known to prolong QTc interval, clinical trials have shown that isavuconazole administration may shorten QTc interval in a dose‐related manner …”
Section: Introductionmentioning
confidence: 99%
“…While azoles as a class effect are known to prolong QTc interval, [1][2][3] clinical trials have shown that isavuconazole administration may shorten QTc interval in a dose-related manner. 4,5 The QT interval is a measure of time in electrocardiograms (ECGs) and describes the duration of the cellular action potential. 6 Due to its variation with heart rate, the QT interval must be corrected before interpretation.…”
Section: Introductionmentioning
confidence: 99%